STRESS-STRAIN BEHAVIOR OF COMPOSITE REINFORCED BEAMS - Shokhrukh Davlyatov; Foziljon Solijonov (Western European Studies, 2025)
The present article presents a comprehensive analysis of research findings on the performance of composite reinforced elements. These elements have gained widespread application in the rehabilitation of concrete structures, both in newly constructed buildings and existing facilities, within the Republic of Uzbekistan and internationally. The study elucidates the mechanical behavior, effectiveness, and practical implications of using composite reinforcement systems in structural restoration
Keywords: composite; basalt; concrete; flexibility